(untitled) (Web of Teachers: Inderscience Research, 2024)
This study explores the effects of various classroom design elements - specifically lighting, furniture arrangement, and color schemes - on student engagement and academic performance in elementary school settings. As education increasingly emphasizes active learning and student well-being, understanding the impact of the physical environment on learning outcomes has become essential. Our analysis draws from recent empirical studies, interviews with educators, and observational data from elementary school classrooms. This paper suggests that design elements like natural lighting, flexible seating arrangements, and calming color schemes enhance student focus and engagement, while also positively influencing academic performance. The results offer insights for educators, school administrators, and architects aiming to optimize learning spaces.